Do Metacognitions of Children and Adolescents with Anxiety Disorders Change after Intensified Exposure Therapy? - Laura Marie Köcher; Verena Pflug; Silvia Schneider; Hanna Christiansen (MDPI AG, 2022)
Metacognitive beliefs have repeatedly proven to play a role in anxiety disorders in children and adolescents, but few studies have investigated whether they change after cognitive behavioral therapy. This longitudinal intervention study explores whether positive and negative metacognitive beliefs in particular change after exposure-focused treatment, and if metacognitive changes predict reductions in anxiety symptoms. A sample of 27 children between 8 and 16 years of age with a primary diagnosis of specific phobia, separation-anxiety disorder or social phobia completed assessments of anxiety symptoms, metacognitive beliefs, worry and repetitive negative thoughts before and after 11 sessions of intensified exposure treatment. Metacognitive beliefs did not change significantly after intensified exposure, but post-hoc power analysis revealed a lack of power here. Change in negative metacognitive beliefs correlated with a change in anxiety symptoms, but did not independently contribute as a predictor variable. Differences between subsamples showed that patients with separation-anxiety disorder scored higher on negative metacognitive beliefs than those with specific or social phobia. Consideration of metacognition, and negative metacognitive beliefs in particular could help us further improve the understanding and treatment of anxiety disorders in children and adolescents and should therefore receive more attention in psychotherapy research.